2020
DOI: 10.3389/fimmu.2020.584364
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling of NLRP3 Identifies Enhanced ATP Binding and Multimerization in Cryopyrin-Associated Periodic Syndromes

Abstract: Cyropyrin-associated periodic syndromes (CAPS) are clinically distinct syndromes that encompass a phenotypic spectrum yet are caused by alterations in the same gene, NLRP3. Many CAPS cases and other NLRP3-autoinflammatory diseases (NLRP3-AIDs) are directly attributed to protein-coding alterations in NLRP3 and the subsequent dysregulation of the NLRP3 inflammasome leading to IL-1β-mediated inflammatory states. Here, we used bioinformatics tools, computational modeling, and computational assessments to explore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 152 publications
(125 reference statements)
0
5
0
Order By: Relevance
“…Decreasing intracellular ATP levels have been correlated with NLRP3 inflammasome activation 32 . A recent computational analysis of NLRP1 to NLRP14 identified amino acid residues that may be involved in nucleotide binding 33 and modeling of NLRP3 suggested enhanced ATP-binding and multimerization in disease related cryopyrin-associated periodic syndrome (CAPS) mutations 34 . Molecular dynamic simulations examined the active site of ADP-and ATP-bound NLRP3 models supporting distinctions in nucleotide-binding domain topology that disseminate on to the global protein structure 35,36 .…”
mentioning
confidence: 99%
“…Decreasing intracellular ATP levels have been correlated with NLRP3 inflammasome activation 32 . A recent computational analysis of NLRP1 to NLRP14 identified amino acid residues that may be involved in nucleotide binding 33 and modeling of NLRP3 suggested enhanced ATP-binding and multimerization in disease related cryopyrin-associated periodic syndrome (CAPS) mutations 34 . Molecular dynamic simulations examined the active site of ADP-and ATP-bound NLRP3 models supporting distinctions in nucleotide-binding domain topology that disseminate on to the global protein structure 35,36 .…”
mentioning
confidence: 99%
“…Activation occurs with diverse agents, including bacterial toxins, microcrystalline substances, ATP, monosodium urate (MSU), calcium pyrophosphate dihydrate (CPPD), silica, asbestos, alum, and hydroxyapatite (HA). Humans harboring one of many NLRP3 point mutations 8 suffer from diseases that result in Familial cold-induced autoinflammatory syndrome (FCAS), Muckle-Wells Syndrome (MWS), Chronic infantile neurologic cutaneous articular (CINCA) syndrome/Neonatal-onset multisystem inflammatory disease (NOMID), which are collectively called cryopyrin-associated periodic syndromes (CAPS) due to constitutively active NLRP3 9 , are more sensitive to activating stimuli. Since none of the agents that activate NLRP3 were shown to bind NLRP3 and are very dissimilar in structure, it is suggested that they trigger a common cellular event that leads to NLRP3 activation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, specific phosphorylation at Ser295 blocks NLRP3’s ATPase activity [8], and several mutations in the vicinity of this phosphorylation site is found in Cryopyrin-associated periodic syndromes (CAPS) [23], which are associated with spontaneous NLRP3- dependent inflammation. The CAPS mutations in the nucleotide binding domain (NBD) appear to have a higher affinity for ATP and thereby to stabilise the open, ATP-bound conformation [125]. For example, the R262W mutation increases speck formation [124], consistent with the predicted increase in ATP-binding affinity [125].…”
Section: Resultsmentioning
confidence: 99%
“…The CAPS mutations in the nucleotide binding domain (NBD) appear to have a higher affinity for ATP and thereby to stabilise the open, ATP-bound conformation [125]. For example, the R262W mutation increases speck formation [124], consistent with the predicted increase in ATP-binding affinity [125]. However, most NLRP3 mutations that decrease the ATPase activity prevent speck formation [124].…”
Section: Resultsmentioning
confidence: 99%